EFFECTS OF PHYSICAL AND HEALTH EDUCATION ON THE VALUE OF BODY MASS INDEX OF PUPILS IN A THIRD GRADE OF ELEMENTARY SCHOOL - Dževad Džibrić; Zumreta Nožinović; Edin Mujanović; Jasmin Bilalić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
One of the risk factors for the occurrence of cardiovascular disease is overweight. Body mass index presents approximate indicator of nutritional status. The aim of this research is to determine effects of physical and health education on the values of body mass index between initial and final measuring within three groups of male respondents, age of 8 ± 6 months. The research included 128 boys, divided in two experimental and one control group. According to obtained arithmetic mean results in applied variables in the beginning and at the end of implemented programs of physical education, as well as according to changes significance tested with T-test for dependent samples it is obvious that programs resulted with significant partial effects in experimental respondent groups